Local Banks and flood risk: The case of Germany - Mario Bellia; Erica Francesca Di Girolamo; Andrea Pagano; Georgios Papadopoulos (European Commission, 2023)
This paper uses a simulation model to evaluate the effects of river flooding events occurring within Germany on regional' banks. Under a 1.5℃ increase in temperature, the impact is overall rather small, even accounting for the devaluation of loans exposed to floods. However, under a 3℃ increase, bank losses can reach 1% of total assets. We show that the implementation of adaptation solutions would be successful in keeping risks at the current level.
Keywords: 330; Physical risk; river flood events; dynamic balance sheet; banking crisis